SARS-COV-2 Infection, Vaccination, and Immune-Mediated Diseases: Results of a Single-Center Retrospective Study - Luchetti Gentiloni, Michele Maria; Paci, Valentino; Marconi, Valentina; Gigli, Marco; Benfaremo, Devis; Sordillo, Raffaella; Macchini, Cristina; Massaccesi, Leonardo; Perna, Gian Piero; Offidani, Anna Maria; Moroncini, Gianluca (Frontiers in Immunology, 2022)
OBJECTIVES The relationship between infections or vaccine antigens and exacerbations or new onset of immune-mediated diseases (IMDs) has long been known. In this observational study, conducted during the COVID-19 pandemic, we evaluated the onset of clinical and laboratory immune manifestations related to COVID-19 or SARS-CoV-2 vaccination. METHODS Three groups of patients were evaluated: A) 584 COVID-19 inpatients hospitalized from March 2020 to June 2020 and from November 2020 to May 2021; B) 135 outpatients with previous SARS-CoV-2 infection, assessed within 6 months of recovery; C) 18 patients with symptoms of probable immune-mediated origin after SARS-CoV-2 vaccination. RESULTS In cohort A we observed n. 28 (4.8%) arthralgia / myalgia, n. 2 (0.3%) arthritis, n. 3 (0.5%) pericarditis, n. 1 (0.2%) myocarditis, n. 11 (1.9%) thrombocytopenia or pancytopenia, and in the follow up cohort B we identified 9 (6.7%) cases of newly diagnosed IMDs after the recovery from COVID-19. In all cases, serological alterations were not observed. and 6 (4.4%) flares of already known IMDs, but in previous good clinical control. In cohort C we report 18 cases of immune-mediated reactions in outpatients: 5 flares of pre-existing IMD after SARS-COV2 infection, and IMDs symptoms temporally closed with SARS-CoV-2 vaccination in 8 healthy subjects (with clinical presentation like classifiable IMD) and in 5 patients affected by an anamnestic IMD. Also in these latter cases, except in 2 healthy subjects, specific serological alterations were not observed. CONCLUSIONS This study suggests that the interplay between SARS-CoV-2 and the host may induce complex immune-mediated reactions, probably induced by the anti-spike antibodies, in healthy people and IMD patients without specific serological autoimmunity. Moreover, our data suggest that the anti-SARS-CoV-2 antibodies generated by the vaccination may cause in healthy subjects clinical manifestations similar to well-definite IMDs. These findings support the hypothesis that the anti-viral antibodies, and not the virus, play a key role in the onset of SARS-CoV-2-related IMDs.